Islet transplantation: present clinical situation and future aspects. - Bretzel, R; Brendel, M; Eckhard, M; Brandhorst, D; Jaeger, C; Hatziagelaki, E; Federlin, K (2001)
Beta-cell replacement either by pancreatic organ or islet cell transplantation is the only treatment to achieve an insulin-independent, normoglycemic state and to avoid hypoglycemic episodes in patients with type 1 diabetes mellitus. This article will review the state-of-the-art in clinical islet cell transplantation at the dawn of the new millennium and will provide an outlook on the basis of extended personal experience.